Strategi Guru dalam Mengajarkan Tari Tradisional pada Siswa Generasi Z di SMA Negeri 7 Semarang - Yanuarifta Haning Palupi; Utami Arsih (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study aims to describe teachers' strategies in teaching traditional dance to Generation Z students at SMA Negeri 7 Semarang, identify the obstacles faced, and efforts to overcome them. Generation Z has strong digital characteristics, thus demanding innovation in arts pedagogy to keep traditional materials relevant. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results show that teachers apply a hybrid strategy that combines direct demonstration methods with the use of digital audiovisual media and social media platforms. The main obstacle found is the low interest of students in traditional culture compared to global popular culture. Teachers' efforts include more dynamic material modifications, a differentiated approach, and the use of creative video-based assignments